Gambaran Pengetahuan Ibu Hamil Tentang Anemia di Wilayah Kerja Puskesmas Perawatan Namrole - Epi Dusra; Maryam Lihi; Siti Rochmaedah (Pusat Riset dan Inovasi Nasional, 2023)
Anemia in pregnancy is anemia due to iron deficiency, iron deficiency anemia in pregnant women is a health problem experienced by women throughout the world, especially in developing countries. The purpose of this study was to describe the knowledge of pregnant women about anemia in the Working Area of ​​the Namrole Health Center. The design used in this study is an analytic research design with a descriptive approach. The population in this study were 80 people. The sampling technique in this study used total sampling. Which means that all populations were used as samples totaling 80 respondents. With data analysis, namely univariate, using a communization process and presented in the form of tables and narratives. It was found that pregnant women with good knowledge were 48 respondents, while 19 respondents had sufficient knowledge, and 13 respondents had less knowledge. It was concluded that almost all of the respondents' knowledge about anemia found in the study was in the good category.